KESESUAIAN LAHAN DAN PRODUKTIVITAS UBI CILEMBU SEBAGAI KOMODITAS UNGGULAN DI KABUPATEN SUMEDANG - Mujiono Mujiono; Kurniawati Sugiyo (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This study aimed to determine the suitability of Cilembu sweet potato land. Land suitability assessment in this study was carried out by a method of matching between crop productivity and land characteristics as parameters with land suitability class criteria that have been prepared based on usage requirements or growing requirements of plants or other commodities evaluated. The results showed that 33% of the area in Sumedang district was physically very suitable for planting Cilembu sweet potato which covers the area of origin of Cilembu sweet potato as well as the surrounding area and areas in the north of the district. High yam productivity is found in the west of the district, including the area of origin of Cilembu sweet potatoes and their surroundings. The relationship of land suitability between Cilembu yam and productivity of Cilembu yam is shown by the alignment areas that are in harmony, (-), not suitable (+) and not suitable. The alignment areas that need attention are the aligned (-) and non-aligned (+) regions.